Aprendizaje colaborativo como estrategia de mediación didáctica para el fortalecimiento de la comprensión lectora en contextos etnoeducativos (2023)
Collaborative learning is a pedagogical strategy that promotes the exchange of knowledge among students and the educational community, with the aim of improving their reading skills and their motivation for reading. This research aims to analyze the reading comprehension processes of primary school students from the institutions I.E.D. Cultural las Malvinas and I.E.D. del Valle, through the use of didactic tools based on collaborative learning. A qualitative approach and a descriptive design were used to collect and analyze the data. The results showed that collaborative learning not only improves the academic performance of students, but also helps them to develop social skills and to overcome memoristic and mechanistic learning. The Collaborative Learning Strategy Program was validated by experts and its positive impact on educational practice was evidenced, by observing the active and cooperative participation of children in reading comprehension activities.